2022
DOI: 10.36513/sigma.v7i2.1276
|View full text |Cite
|
Sign up to set email alerts
|

Proses Berpikir Siswa Berkebutuhan Khusus Dalam Pemecahan Masalah Matematika Menggunakan Alat Peraga

Abstract: This study aims to describe the thinking process of Attention Deficit Hyperactivity disorder (ADHD) students in solving mathematical problems using teaching aids. This research is a qualitative research that uses a descriptive research methodology. The subjects of this study were students at one of the Special Schools (SLB) in Cirebon City as many as 3 ADHD students who had received learning using visual aids. Then the subject selection technique used purposive sampling technique. The main instrument in this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
9

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
4
0
9
Order By: Relevance
“…This is in accordance with the results of Hidayat & Noer (2021) that students who have high self-efficacy are able to solve problems carefully, but on the contrary students who have low self-efficacy tend to be less good at solving problems. Likewise, based on Subaidi (2016) concluded that students in the lower selfefficacy category tend to hesitate and give up easily in solving math problems. In addition, students also have the view that a difficult problem is something that must be avoided.…”
Section: Mathematical Literacy In the Low Self Efficacy Categorymentioning
confidence: 99%
“…This is in accordance with the results of Hidayat & Noer (2021) that students who have high self-efficacy are able to solve problems carefully, but on the contrary students who have low self-efficacy tend to be less good at solving problems. Likewise, based on Subaidi (2016) concluded that students in the lower selfefficacy category tend to hesitate and give up easily in solving math problems. In addition, students also have the view that a difficult problem is something that must be avoided.…”
Section: Mathematical Literacy In the Low Self Efficacy Categorymentioning
confidence: 99%
“…Pernyataan ketiga membahas mengenai menyerah dalam mempelajari materi yang sulit, skor persentase sebanyak 33,33% termasuk kedalam kriteria kurang, dimana skor tersebut menunjukkan bahwa mahasiswa memiliki sikap pantang menyerah dalam mempelajari suatu materi yang sulit hingga dapat memahami apa yang sedang dipelajari. Sikap pantang menyerah sangat diperlukan pada proses pembelajaran karena merupakan sikap tidak patah semangat dalam menghadapi rintangan untuk mewujudkan tujuan (Subaidi, 2016). Menurut Dinata (2019) Indikator yang keenam merupakan antusias atau dorongan.…”
Section: Hasil Dan Diskusiunclassified
“…Hal ini di dukung dengan hasil penelitian Subaidi (2016) dimana peserta didik dengan Self-Efficacy yang lemah atau rendah cenderung rentan dan mudah menyerah menghadapi masalah matematika tersebut, mengalami kesulitan dalam memecahkan tugas dan masalah matematika tersebut, dan kegagalan memecahkan masalah matematika tersebut dianggap karena kurangnya kemampuan matematikanya. Namun hal ini kontra dengan hasil penelitian sebelumnya Ulya (2015) menunjukkan koefisien korelasi antara gaya kognitif dengan kemampuan pemecahan masalah peserta didik sebesar 0,624 yang berarti bahwa terdapat hubungan positif dalam taraf tinggi antara gaya kognitif peserta didik dengan kemampuan pemecahan masalah peserta didik.…”
Section: Hasil Dan Pembahasanunclassified